Mapping time : illustrated by Minard's map of Napoleon's Russian Campaign of 1812 - Kraak, M. J. (Esri Press, 2014)
Mapping Time: Illustrated by Minard's Map of Napoleon's Russian Campaign of 1812 considers the cartographic challenge of visualizing time on a map. Inspired by graphic innovator Charles Minards classic map of Frances disastrous invasion of Russia, this book combines historical and geographic analysis with cartographic visualizations of mapping change over time. It includes more than 100 full-color illustrations.